(untitled) (Research, Society and Development, 2022)
To evaluate through a literature review the malocclusions and the adherence to orthodontic treatment in autistic patients, as well as to investigate and identify the difficulties faced during treatment and what changes may occur in their development. This is a literature review from the search for scientific publications indexed in the electronic databases made databases Naional Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Google Scholar, Virtual Health Library (VHL), between the period 2009 to 2022. Given the findings of the selected studies, it can be observed that there are significant occlusal changes, and oral conditions in patients with autistic spectrum disorder and the dental surgeon must be trained to improve the quality of oral health of the TEA patient and the difficulties that will be in relation to treatment. This study allowed us to reflect that it is of great need that the dental surgeon together with a multidisciplinary team have plans to improve the life of the patient and his family, adapting the same in a dental routine aimed at the prevention of oral diseases, and bringing the most comprehensive way possible a better quality of life.